Aneurysmal bone cyst of the parietal bone: case report - Ekici, Mehmet Ali; Ozbek, Zuhtu; Kazanci, Burak; Guclu, Bulent (The European Research Journal, 2015)
Aneurysmal bone cysts are locally destructive, vascular, multicystic benign tumors of bone, which are usually located on metaphysis. Cranial aneurysmal bone cysts are uncommon. We report a 18-year-old girl with a 3-month history of skull asymetry and headache which was not relieved by analgesic drugs. Computed tomography scan demonstrated an osteolytic skull lesion of the right parietal bone and the neural tissue that was compressed without midline shift. The patient had complete recovery after total excision of the lesion. We also discuss the etiology, pathogenesis, pathologic features, imaging characteristics and treatment of cranial aneurysmal bone cysts.